Changes in hormonal levels during the season in elite female triathletes - Rietjens, G. J.; Keizer, H.; Kuipers, H. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
To maximize their performance capacity many athletes reach a phase were physical exercise and associated cellular disturbances are not balanced by adequate recovery. This may lead to short-term and/or long-term decreases in performance. It is well described that exercise is a powerful acute stimulus of the release of several hormones (growth hormone (GH), adrenocorticotropic hormone (ACTH), cortisol and prolactin (PRL). On the other hand, several pathological conditions associated with severe psychic stress, the secretion of GH, ACTH, cortisol and PRL is blunted. It is still not clear if this release is also suppressed during periods of extremely heavy training. In this pilot study we made an attempt to investigate changes in hormone levels, which are associated with severe training-induced fatigue. For this purpose eight elite world ranked male and female Olympic distance tri-athletes were investigated during an all out incremental bicycle ergometer test before the start of the training season and three times during their preparation period of heavy training towards the World Cup season and the centennial Olympic games. Blood samples for hormones were collected at rest, during the bicycle test and direct after cessation of the test. The preliminary results of four (female) athletes presented here, showed a decrease in GH (fig. 1A) and ACTH (fig. 1B) levels during (sub-maximal and maximal intensity) exercise during their training period. The decrease in GH levels were closely related to the subjects decrease of maximal heart rate (181 / min in test 1 to 176 / min in test 4) and maximal lactate levels (13.6 mmol/l in test 1 to 9.7.mmol/l in test 4) during the same period. These findings corresponded with the feelings of the subjects (increased fatigue and decreased vigor) whereas this relation was not that strong for ACTH. No clear alterations were found in cortisol and PRL. In conclusion GH levels seem to correlate ell with impairment in exercise capacity